Expanding the Accessible Forest Areas by Improving Forest Road Standards and Utilizing Mobile Fire-fighting Teams - Kasap, Caner Yavuz; Akay, Abdullah Emin; Aricak, Burak; Bilici, Ebru; Uçar, Zennure; Erkan, Neşat; Guney, Coskun Okan (Forest Engineering and Technologies Platform, 2024)
In Turkiye, insufficient technical standards of the forest roads limit the speed of the fire truck, leading to increase in the arrival time of the initial response team to the fire areas. Improving forest road standards will increase the design speed and expand the accessible forest areas within the critical response time. In this study, the effect of improving forest road standards on expanding accessible forest areas was investigated. Considering the forest areas in Antalya Forestry Regional Directorate in Turkiye, accessible areas by the stationary initial response teams (103) and mobile teams (71) were determined from the existing road network, and then, the possible increase in the accessible forest areas was investigated when the road standards are improved. Within the scope of the study, the impact of mobile teams used in emergencies on forest areas reached during the critical response period was also evaluated. According to the results, in the scenario where current road standards and stationary teams were evaluated, it was determined that only 59.54% of the forest areas could be reached by initial response teams during the critical response time. When the road standards were improved, this rate increased to 71.69%. On the other hand, when the current road standards and stationary and mobile teams were evaluated together, it was determined that initial response teams could reach 70.40% of the forest areas during the critical response time, and if road standards were improved, this rate increased to 78.17%. Also, utilizing mobile teams increased the accessible forest areas within the critical response time by 9.03%. The results have shown that improvements in road standards and the presence of mobile teams have a very effective role in combating forest fires. © Copyright 2024 by Forest Engineering and Technologies Platform on-line at https://dergipark.org.tr/en/pub/ejfe.
Keywords: forest roads; GDF; GIS; network analysis; stationary and mobile team; Wildfires